WiFi positioning overview. (1st January 2011) - Liao, Lingxia; Lin, Kai; Wang, Xiaofei; Lai, Xiaorong; Vuong, Son T.
As the swift development and deployment of WiFi networking infrastructure with the lower price to provide the wider coverage, WiFi-based positioning approaches have been one of the 'best practices' in both outdoor and indoor environment. In this paper, an overview of various approaches for WiFi-based positioning is presented. The WiFi-based positioning approaches are categorised into cell-ID, angle of arrival (AOA), received signal strength (RSS), time of arrival (TOA) and time difference of arrival (TDOA). The basic idea and ranging accuracy are presented to compare the different approaches. As the most practical methods, fingerprinting and TDOA approaches are elaborated and some advanced methods based on them are also provided to show the improvement. The different approaches are basically evaluated by their ranging accuracy, but the system privacy and scalability, as the other two key directions to evaluate a positioning system, are also discussed in this paper.